The power of push factors on academic’s brain drain in higher education system in Sudan - Ajeeb, Hafiz Ahmed (Technium Social Sciences Journal, 2021)
This study aimed to investigate the level of push factors of brain drain among the academics in the Sudanese higher education system. The status of a university environment, lack of research policy, and intellectual freedom led Sudanese higher education institutions to lose a growing number of highly qualified professors. The study aspires to identify the power of work environment, career development, livelihood, and political factors in higher education and to what extent do these antecedents predict brain drain. The study used a convergent mixed research approach. To that end, 380 participants were taken through simple random sampling techniques. Quantitative data was collected from teachers using closed-ended questions. At the same time, vice-chancellors, faculty deans, and department heads were interviewed. Quantitative data was analyzed through mean scores, one-sample t-test, and linear regression analysis and ANOVA respectively. Qualitative data was analyzed through thematic narration. The study found that addressing push factors by improving the work environment to meet employers’ expectations, going through career development barriers, stabilizing the political environment, restructuring wages and remunerations could control the brain drain. It is also found that improved governance creates an ideal academic environment by maintaining relevant legislation, supplying funds for activities, and pursuing training and capacity-building initiatives to prevent brain drain. The study recommended that leaders and stakeholders enforce proper strategies and policies for environmental improvement and encourage private sector investment in higher education. Also, policymakers and funding agencies should pass legislation to fill the wage gap, which absorbs migration.